Kemampuan Berpikir Kreatif Matematis Siswa SMA Kelas X pada Materi Eksponen - Eka Putri Regina; Ucik Fitri Handayani (Kilau Publishing, 2024)
Mathematical creative thinking involves using diverse ideas to solve problems, generating unique solutions, and developing high-level cognitive skills. The purpose of this research is to describe the mathematical creative thinking ability of students of SMAN 1 Bantur Malang by using indicators consisting of three indicators, including (a) fluency, (b) flexibility, and (c) novelty. This research method is descriptive qualitative with the research subjects are 20 grade X students. Data collection was done through tests and interviews. The instruments used in this study were two questions about exponent material. The results of the analysis show that the potential of students' mathematical thinking and students' creative thinking is still not optimal. The percentage of students who can fulfill the fluency indicator is 50% which is in the low category, while the percentage of students who can fulfill the flexibility indicator is 25% and the novelty indicator is 5% which is in the very low category. The lowest indicator that can be fulfilled by students is the novelty indicator, while the highest indicator that can be fulfilled by students is the fluency indicator. Teachers are advised to familiarize students with solving problems that have different answers and ways/strategies of solving them so that creative thinking skills can be trained.